Aggressive angiomyxoma of the vulva - Debabrata Barmon; Amal Chandra Kataki; J D Sharma; Judy Bordoloi (Wolters Kluwer Medknow Publications, 2012)
Aggressive angiomyxoma is a rare, benign neoplasm occurring in 3 rd to 5 th decade of life that can be mistaken both clinically and on microscopy for several other conditions, it should be included as a differential diagnosis for any vaginal mass. These lesions have a predilection for female pelvic soft tissues, slow in growth, and are characterized histologically by a predominantly myxoid stroma and an abundance of thin and thick walled vascular channels. This is a deep soft tissue tumor, which as the name suggests, may have a locally aggressive course. Most tumors occur in women and are large, usually greater than 10 cm, slowly growing, and painless. Standard of care treatment for angiomyxoma has been surgery. Some authors believe that it is the only possible treatment, but surgery is often radical and can be mutilating, with massive blood loss.